The Relationship Between Mothers Knowledge and Attitudes Related to The First 1000 Days of Life With The Incidence of Stunting - Hesteria Friska Armynia Subratha; Pebriyani, Ni Putu Nita; Made Ila Miranda Hary; Made Diva Aprliasih Arya Putri; Ni Luh Erlya Lionita (Babali Nursing Research, 2024)
Introduction: Stunting is a disruption in the growth and development of children due to chronic malnutrition and recurrent infections, which is characterized by their length or height being below standard. In 2021, stunting in Buleleng Regency will reach 8.9% from the prevalence rate in 2019 of 22.05%. Based on Buleleng health data in 2021, in Banjar District there were 188 toddlers experiencing stunting out of a total of 1462 toddlers with a percentage of 12.86%. This research aims to determine the level of knowledge and description of maternal attitudes as well as the relationship between maternal knowledge and attitudes regarding the first 1000 days of life and the incidence of stunting in Banjar District. Methods: This research was conducted using a cross sectional approach with a sample of mothers who had children aged 0-5 years who were stunted in Banjar District. Data was collected by conducting structured interviews and distributing research questionnaires which will be analyzed using qualitative analysis. Results: The findings of this study identified three categories of maternal knowledge: mothers with a high level of knowledge (9.52%), mothers with a moderate level of knowledge (41.27%), and mothers with a low level of knowledge (49.21%). And than the P value 0.000 < 0.05 that indicated correlation between the knowledge and attitudes of mothers regarding 1000 HPK nutrition. Conclusion: This study demonstrates a correlation between the knowledge and attitudes of mothers regarding 1000 HPK nutrition in Kecamatan Banjar. The findings indicate a moderately strong positive link between these variables.